The Effect of Marketing Mix ‘7P (Product, Price, Place, Promotion, People, Process, and Physical Evidence) on Customer Loyalty of Nasi Jamblang Bu Nur Cirebon - Indi Nirawati; Jimmy Hasoloan (Greenation International Journal of Economics and Accounting, 2024)
Research on the effect of the marketing mix on customer loyalty has been conducted before in various business contexts. In the context of this study, UKM Nasi Jamblang Bu Nur was chosen because it is one of the rice stalls that is quite famous in Cirebon and has a long history. Nasi Jamblang Bu Nur is included in the category of suitable variables in the marketing mix. This shows that Nasi Jamblang Bu Nur has done an excellent job implementing the Marketing Mix with Product, Price, Place, and Promotion indicators, especially those related to product indicators. On the other hand, promotion indicators still require improvement.  In Nasi Jamblang Nur, the Customer Loyalty Variable is included in the Very Good group. This indicates that Nasi Jamblang Nur customers are loyal to using Nasi Jamblang Nur for their needs. This is indicated by signs such as often buying the same product, buying many items, referring friends, and difficulty moving to competing products or other products. The marketing mix positively influences customer loyalty, so any increase in the marketing mix that includes indicators of place, price, product, and promotion is not will increase customer loyalty. Customer loyalty will decrease if the marketing mix decreases.